2011
DOI: 10.1080/00051144.2011.11828410
|View full text |Cite
|
Sign up to set email alerts
|

Task Based Bilateral Control for Microsystems Application

Abstract: Original scientific paperDesign of a motion control system, convenient for a wide range of applications in industry, space, biology, medicine, particularly including more than one physics environment is very important. Well known control architectures like trajectory tracking, compliance control, interaction force control are scientific milestones which has common control task: to maintain desired system configuration. In this concept, motion control system can be an unconstrained motion-performed interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that this bilateral control theory can attain high transparency. Then, the applications of the principle of acceleration-based bilateral control are expected to advance the motion control technology for a haptic communication over the network [10], a high precision micro manipulation [11,12], a novel skill preservation [13], an innovative medical treatment system [14], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that this bilateral control theory can attain high transparency. Then, the applications of the principle of acceleration-based bilateral control are expected to advance the motion control technology for a haptic communication over the network [10], a high precision micro manipulation [11,12], a novel skill preservation [13], an innovative medical treatment system [14], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral control is a method of teleoperation control with haptic feedback and has been considerably developed to apply in robotics, medicine, space, nuclear power plant, mine cleaning and so on [1]- [5]. In a bilateral control system, human operator is in contact with the master device and the slave device is in contact with the environment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are robots for space, for atomic power plant, for micro-manipulation, etc [1]. Developing performance of the teleoperated robots, it will be possible for human to work in such a ultimate environment with safety.…”
Section: Introductionmentioning
confidence: 99%